Flowering in grassland predicted by CO2 and resource effects on species aboveground biomass. (28th January 2018) - Fay, Philip A.; Aspinwall, Michael J.; Collins, Harold P.; Gibson, Anne E.; Gill, Richard H.; Jackson, Robert B.; Jin, Virginia L.; Khasanova, Albina R.; Reichmann, Lara G.; Polley, H. Wayne
Abstract: Continuing enrichment of atmospheric CO2 may change plant community composition, in part by altering the availability of other limiting resources including soil water, nutrients, or light. The combined effects of CO2 enrichment and altered resource availability on species flowering remain poorly understood. We quantified flowering culm and ramet production and biomass allocation to flowering culms/ramets for 10 years in C4 ‐dominated grassland communities on contrasting soils along a CO2 concentration gradient spanning pre‐industrial to expected mid‐21st century levels (250–500 μl/L). CO2 enrichment explained up to 77% of the variation in flowering culm count across soils for three of the five species, and was correlated with flowering culm count on at least one soil for four of five species. In contrast, allocation to flowering culms was only weakly correlated with CO2 enrichment for two species. Flowering culm counts were strongly correlated with species aboveground biomass (AGB; R 2 = .34–.74), a measure of species abundance. CO2 enrichment also increased soil moisture and decreased light levels within the canopy but did not affect soil inorganic nitrogen availability. Structural equation models fit across the soils suggested species‐specific controls on flowering in two general forms: (1) CO2 effects on flowering culm count mediated by canopy light level and relative species AGB (species AGB/total AGB) or by soil moisture effects on flowering culm count; (2) effects of canopy light level or soil inorganic nitrogen on flowering and/or relative species AGB, but with no significant CO2 effect. Understanding the heterogeneity in species responses to CO2 enrichment in plant communities across soils in edaphically variable landscapes is critical to predict CO2 effects on flowering and other plant fitness components, and species potential to adapt to future environmental changes. Abstract : Flowering is the first step in producing genetically variable offspring. In a long‐term experiment, CO2 enrichment explained up to 77% of flowering culm counts across varying soils in several widespread grassland species. Structural equation models indicated that for some species, CO2 effects on flowering culm count were mediated by light availability, species relative abundance, and/or soil moisture. For others, flowering culm counts were related only to relative abundance and light or soil nitrogen. Understanding varying species responses to CO2 enrichment across soils is critical to predict CO2 effects on species potential to adapt to future environmental changes.